The Effect of Behavioral Bias on Investment Decisions Through Risk Perception as a Mediating Variable - Setiya Amelia Vega; Nur Anisah (Proceeding International Conference on Digital Education and Social Science, 2025)
This research seeks to examine how three behavioral biases—dispositioneeffect, herding behavior, and blue chippstock bias—oniinvestment decision, considering risk perception as a mediating factor among retail investors PT. Phintraco Sekuritas Surabaya. The scope of this study includes testing the direct and indirect influences between variables through an explanatory quantitativeeapproach. Data was gathered from 100 participants throughaa Likerttscale questionnaireeand subsequently analyzed utilizing data quality assessments, classical assumption evaluations, multipleelinear regression, and Sobel tests to investigate the mediating effect. The results suggest that herd behavior and a preference forrblue-chip stocks have a significant influenceeon the perception of risk, while the dispositioneeffect has no influence. In testing investment decisions, only herding behavior and risk perception showed a significant effect, while the effects of disposition and blue chip stock bias had no direct effect. The Sobel test has shown thattrisk perceptionnmediates the relationshippbetween herding behavior and the blue-chip stocks biasiin investment decisions, but not the influence of disposition effect. Overall, the study concludes that herding behavior and perceptions of blueechip stocks shape riskpperception, which ultimately influences investmenttdecisions, thus proving that risk perception is an important mediator in the retail investor behavior model.